Mutations in the Progesterone Receptor (PROGINS) May Reduce the Symptoms of Acute Hepatitis E and Protect Against Infection - López-López, Pedro; Rivero-Juarez, Antonio; Frias, Mario; Machuca, Isabel; Caballero-Gómez, Javier; Olivas, Israel; Camacho, Angela; Risalde, María de los Angeles; García-Bocanegra, Ignacio; Rivero, Antonio (Frontiers in Microbiology, 2019)
Background: Mutations in the progesterone receptor (PR) gene, PROGINS, have been studied in relation to hepatitis E virus (HEV) infection. Patients with the PROGINS gene may develop a worse clinical course of hepatitis E. The aim of our study was to evaluate the influence of PROGINS on the susceptibility to and the clinical course of HEV infection in HIV patients. Methods: This study included patients with HIV who were evaluated in previous prospective studies for the prevalence and incidence of HEV. The following three groups of patients were studied: i) never infected, ii) past infections and iii) recently infected. We determined the PR genotype to evaluate the proportion of patients who were homozygous for PROGINS according to HEV infection. We also compared the proportion of PROGINS carriers with a recent HEV infection according to their symptomatology. Results: In this study, 311 patients infected with HIV were included. Of those patients, 198 were homozygous wild type (63.7%), 91 were heterozygous (29.3%), and 22 were homozygous PROGINS (7.1%). We found that the homozygous PROGINS genotype in women was associated with a lower HEV seroprevalence. In addition, in patients with a recent HEV infection, none of those homozygous for PROGINS presented symptoms. Conclusions: The PROGINS mutation plays a protective role against HEV infection and is associated with subclinical infection in HIV-infected patients, particularly women.